Evaluasi Pengetahuan dan Persepsi Obat Batuk Swamedikasi oleh Perokok - Amelia Lorensia; Ananta Yudiarso; Rizkia Arrahmah (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Coughing is one of the most common symptoms in smokers. Smokers who experience a lot of cough arecaused by exposure to cigarette smoke that enters the respiratory tract. The purpose of this study was to determinehow smokers perceive symptoms of cough, use of cough medicine, and self-medication services performed by pharmacists.This study began in March to July 2016. This study used the mixed method method that uses sequentialexplanatory research design. The research sample involved amounted to 100 people, and 12 studies conductedfor interviews were conducted to obtain supporting data. The sample were active smokers aged 18-40 years withmale and female sex who had experienced coughing and had used cough medicine. The results obtained are thetype of cough experienced by smokers is cough with phlegm and cough is not phlegm depending on the categoryof smokers. The use of cough medicine is one of the most common ways for active smokers to reduce the incidenceof coughing. However, there are still many smokers who are wrong in choosing and using cough medicine becausethe knowledge that active smokers have for coughing is still inadequate.